Impact of a lifestyle physical activity intervention on school going children's physical activity participation - Figaji, Tamara Ann (University of the Western Cape, 2014)
Magister Scientiae (Physiotherapy) - MSc(Physio) === Associated with physical inactivity and obesity are numerous other health risks which have become a major health concern. A steady decrease in the levels of physical activity during childhood and adolescents have been noted in various parts of the world. The picture of low physical activity levels in developed countries is no different in developing countries. Children spend the majority of their day at school therefore a school setting is ideal to conduct physical activity intervention studies The primary aim of this study was to measure the effect of an intervention programme on the physical activity participation levels among school going children and adolescents. The study was carried out at an urban independent Catholic school. The sample, which was conveniently selected, which included 100 learners from grade 5 to 7 with parental consent. A quantitative approach using a quasi-experimental design was used in this study. Baseline data included levels of physical activity participation, Body Mass Index (BMI), hip-waist ratio, and socio-demographic variables. Physical activity was assessed with the Modifiable Activity Questionnaire for Adolescents. The Promoting Lifestyle activity for Youth (PLAY) programme was implemented at the school. This process-oriented programme shifts the focus from fitness toward regular participation in daily physical activity, and it is not intended to replace a comprehensive physical education programme. === South Africa